Mobile-Based Psychomotor and Affective Development Application for Students - Miftah, Muhammad; Syahrir , Muhammad; Novia Wati, Risa; Fadia Septariani, Sella (Journal of Islamic Communication and Counseling, 2024)
Developing affective and psychomotor values in children is highly important and should be prioritized in educational objectives. This is beneficial for shaping individuals who are not only intellectually intelligent but also possess directed skills and a positive attitude towards others, as high cognitive achievement is insufficient without accompanying skill and behavior values. The author developed an application to improve students' psychomotor and affective abilities. The waterfall method was utilized in the creation of the application. Features were designed to facilitate good communication between parents and teachers in developing children's psychomotor and affective skills. Twelve features are purposed to assist parents and teachers in supporting the optimal development of children's competencies based on parenting dimensions.